2019
DOI: 10.26434/chemrxiv.8178926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bimetallic Radical Redox-Relay Catalysis for the Isomerization of Epoxides to Allylic Alcohols

Abstract: Organic radicals are generally short-lived intermediates with exceptionally high reactivity. Strategically, achieving synthetically useful transformations mediated by organic radicals requires both efficient initiation and selective termination events. Here, we report a new catalytic strategy, namely bimetallic radical redox-relay, in the regio- and stereoselective rearrangement of epoxides to allylic alcohols. This approach exploits the rich redox chemistry of Ti and Co complexes and merges reductive epoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…31 Na2CO3 was barely soluble in the mixed solvent of DMF/MeCN (1:1), explaining its failure in promoting the reaction of [Co III ] with 2 under the static conditions employed for the CV testing. Based on the results of this study and previous work, 31,35 a possible mechanism for the electrocatalytic allylic C-H alkylation reaction was proposed (Fig. 5d).…”
Section: Resultssupporting
confidence: 69%
“…31 Na2CO3 was barely soluble in the mixed solvent of DMF/MeCN (1:1), explaining its failure in promoting the reaction of [Co III ] with 2 under the static conditions employed for the CV testing. Based on the results of this study and previous work, 31,35 a possible mechanism for the electrocatalytic allylic C-H alkylation reaction was proposed (Fig. 5d).…”
Section: Resultssupporting
confidence: 69%
“…2 While our protocol con- verted 1AL to 2AL, ring opening of a similar cholesterol (R' = Bz) with titanocene furnished a tertiary radical, and the adjacent hydrogen was abstracted by a cobalt catalyst leading to an allylic alcohol. 38 These contrasting results demonstrated that our catalytic protocol is complementary to conventional methods with titanocene.…”
mentioning
confidence: 95%
“…verted 1AL to 2AL, ring opening of a similar cholesterol (R' = Bz) with titanocene furnished a tertiary radical, and the adjacent hydrogen was abstracted by a cobalt catalyst leading to an allylic alcohol. 38 These contrasting results demonstrated that our catalytic protocol is complementary to conventional methods with titanocene.…”
mentioning
confidence: 95%